Rice Farming Applicator Robot Control System Based on Radio Wave Communication Using Flysky Fs-iA6 Type Remote Control and Arduino Mega - Ridwan Siskandar; Tineke Mandang; Wawan Hermawan; Irzaman Irzaman (The University of Lampung, 2025)
This research focuses on designing a control system for pesticide applicator robots on rice plants. Control is carried out via radio wave communication using a transmitter-receiver (Flysky FS-iA6 2.4 GHz). The remote can control the robot wheel (forward, backward and turn), boom sprayer (raise-fall and open-close), and spray pump. The research method is carried out using the waterfall model because it is under the needs that require a sequential flow in the process. The test results show that the use of a bevel gear gearbox can increase the torque value up to 3 times. The use of 4 electric motors further increases the stability of the robot's movement (RPM and torque) when given the maximum load of the robot. The boom sprayer successfully opens-closes and fluctuates smoothly at the optimum value of PWM 50 and voltage 2.35. The time required for the boom sprayer to open-close, and rise-fall is 30 s. The relay which functions as a switch is successfully controlled, so that the pump can be activated and deactivated in mode 2 at the input. Transmitter-receiver communication test was successfully carried out. Transmitter-receiver communication is capable of up to a distance of < 150 m. Input mode 1 on the transmitter successfully controls the boom sprayer. Input mode 2 successfully controls the motion of the wheels and pump.